2020
DOI: 10.1002/ccr3.2732
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypersensitivity reaction to etoposide phosphate: A case report

Abstract: Hypersensitivity to etoposide phosphate has rarely been documented. We report a case of severe hypersensitivity reaction to etoposide phosphate in an old man. The patient experienced anaphylactic shock and has been hospitalized in intensive care unit. Vigilance is required regarding potential severe reactions with etoposide phosphate formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Immediately upon initiation of an etoposide phosphate infusion, a man experienced a severe hypersensitivity reaction leading to anaphylactic shock requiring administration to the intensive care unit. 21 Towards the end of a one-hour infusion of etoposide phosphate, a young girl suffered a hypersensitivity reaction. 22 The following day, etoposide base was substituted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immediately upon initiation of an etoposide phosphate infusion, a man experienced a severe hypersensitivity reaction leading to anaphylactic shock requiring administration to the intensive care unit. 21 Towards the end of a one-hour infusion of etoposide phosphate, a young girl suffered a hypersensitivity reaction. 22 The following day, etoposide base was substituted.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, etoposide phosphate has also been implicated in causing hypersensitivity reactions. [18][19][20][21][22] Several authors have suggested that dextran 40, which is an excipient in the formulation of etoposide phosphate, could be responsible for the observed infusion reactions. 21,22 Severe hypersensitivity reactions to clinical dextrans have been recorded since the 1960s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another form of VP16, etoposide phosphate is a water-soluble prodrug with no trace of polysorbate 80 that has successfully proven a good substitute agent after etoposide HSR [ 87 , 88 ]. Despite being extremely rare, more recently, severe anaphylactic-like reactions to this newer formulation have also been described [ 89 ]. Regarding teniposide, an older comprehensive analysis showed an incidence of 6.5% of HSR to VM-26, with a higher percentage in children with neuroblastoma and brain tumors, compared to hematologic malignancies [ 90 ].…”
Section: Antineoplastic Therapy Involved In Hypersensitivity Reactionsmentioning
confidence: 99%
“…pediatric leukemia) and more rarely reaction to etoposide itself are discussed in the literature. [1][2][3][4][7][8][9][10][11][12][15][16][17] Etoposide can be administered undiluted or diluted. In the latter case, it should be diluted in dextrose 5% or normal saline to obtain a concentration between 0.2 and 0.4 mg/mL.…”
Section: Introductionmentioning
confidence: 99%